Rotting Banyu dan Suwinih sebagai Penerapan Pajak dalam Pemanfaatan Air Irigasi Subak - Si Gede Bandem Kamandalu; Ni Ketut Puji Astiti Laksmi; Zuraidah; Hedwi Prihatmoko (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
Farming is one of the efforts made by humans to get food. Agricultural activities continue to experience development and dynamics starting from simple level to more complex level. The complexity of agricultural activities has been mentioned in inscriptions issued during the reign of the ancient Balinese kingdoms of the 9th to 15th centuries which was indicated by the existence of agriculture based on a regular pattern. This research focuses on discussing the implementation of taxes in the use of subak irrigation water both during the Ancient Bali period and today. The data collection process in this study includes literature review, interviews, and observation. The data that has been collected is then processed using a descriptive-qualitative analysis, this analysis emphasized on the quality of the description in its presentation. The ethnoarchaeological analysis is also used in this study, the purpose of which is to provide an analogy to the implementation of taxes in the subak area. The result of this study indicated that there were conceptual similarities between rotting banyu and suwinih which is a form of implementation of water tax on paddy field management. Keywords: rotting banyu; suwinih; irrigaton; subak gede pulagan-kumba